2003
DOI: 10.1038/sj.tpj.6500194
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopaminergic and serotonergic genes with tardive dyskinesia in patients with chronic schizophrenia

Abstract: Tardive dyskinesia (TD) is a long-term adverse effect of antipsychotic drugs that are dopamine D2 receptor blockers. Serotonin receptor antagonism has been proposed as a common mechanism contributing to the low extrapyramidal side effect profile of atypical antipsychotic drugs. We evaluated candidate dopamine and serotonin genes for association with drug-induced TD. We examined three polymorphisms in the dopamine D2 receptor gene (DRD2), two sites in the 3' region of the dopamine transporter (DAT) gene, two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 47 publications
2
38
1
1
Order By: Relevance
“…The association of the dopamine D4 receptor (DRD4) with the development of TD has been studied less than DRD2 and DRD3, with only 2 studies having been published. Lattuada et al [14] reported a marginally significant association between the short allele of the DRD4 variable number of tandem repeat polymorphism on exon III and TD, while Segman et al [15] reported no association between them. Most recently, Srivastava et al [16] reported that a 120-bp duplication marker that is 1.2 kb upstream from the initiation codon of the DRD4 gene showed a significant genotypic association with TD.…”
Section: Introductionmentioning
confidence: 99%
“…The association of the dopamine D4 receptor (DRD4) with the development of TD has been studied less than DRD2 and DRD3, with only 2 studies having been published. Lattuada et al [14] reported a marginally significant association between the short allele of the DRD4 variable number of tandem repeat polymorphism on exon III and TD, while Segman et al [15] reported no association between them. Most recently, Srivastava et al [16] reported that a 120-bp duplication marker that is 1.2 kb upstream from the initiation codon of the DRD4 gene showed a significant genotypic association with TD.…”
Section: Introductionmentioning
confidence: 99%
“…The recent identification of genetic polymorphisms for some of the primary targets of psychotropic drug action (for example, serotonin transporters for the selective serotonin reuptake inhibitors, dopamine and serotonin receptors for the antipsychotics) have enabled investigators to evaluate the potential relationship of these polymorphisms to neurochemical measures, treatment response, and side effect induction (eg Smeraldi et al, 1998;Pollock et al, 2000;Murphy et al, 2003;Kaiser et al, 2001;Segman et al, 2003). The integration of genetic methods with in vivo neurobiologic techniques (neuroendocrine and neuroimaging studies) represents a unique opportunity to understand the functional consequences of specific genetic polymorphisms, which may have implications for the understanding of the mechanisms underlying the variability in acute and chronic psychotropic drug response.…”
Section: Introductionmentioning
confidence: 99%
“…Five studies could not be included either because categorical data were not used 61,69 or data were not reported. 56,59,60 No large or significant pooled OR was found for the alleles or genotypes for Ser311Cys 58,[66][67][68] or for À141C Ins/Del 27,66-68 (results available upon request). There was no evidence of heterogeneity or publication bias, although there was some indication for publication bias for the Ser311Cys allele comparisons (B = 3.56, 95% CI: À0.25 to 7.37, P = 0.057).…”
mentioning
confidence: 99%